Benefits of Early Second Language Acquisition - rizki amelia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Second language acquisition is the study how second languages are learned and the factors that influence the process. Exposing your child to a second language acquisition while young allows him or her to optimize his or her learning potential, helping to shape the brain at its most flexible stage. Young children are uniquely suited to learning a second language. Learning a second language at a young age is cognitively as easy as learning a first language. This paper examines some benefits of early second language acquisition.